IMMUNOLOGICAL ASPECTS OF ESSENTIAL HYPERTENSION - Yanina Rimovna Timasheva (Медицинская иммунология, 2019)
According to modern concept of the etiopathogenesis of essential hypertension, immune cells play an important role in its development. Mediators produced by immunocompetent cells participate in the initiation and maintenance of chronic systemic inflammation and promote the development of vascular remodeling which is an important part of the pathogenesis of the disease and target organ damage. The immune mechanisms underlying blood pressure elevation include the activation of innate and adaptive immune cells. Endothelial damage triggers an inflammatory cascade, causing migration of the immune cells to the inflammatory site, mediated by chemokines and adhesion molecules. Macrophage infiltration of perivascular tissue contributes to impaired vasodilation and damage to target organs due to the production of active forms of oxygen. Angiotensin II also causes T-cell infiltration of perivascular adipose tissue and adventitia and an increased production of tumor necrosis factor alpha and interferon gamma. In addition, T-lymphocytes express the mineralocorticoid receptor involved in the development of systemic hypertension. An important role in the progression of hypertension belongs to interleukin-17, which is involved in blood pressure elevation and vascular remodeling. The review also contains data on the effect of gut microbiota on the regulation of blood pressure and the development of hypertension.